Investigational drugs for fracture healing: preclinical & clinical data. (3rd May 2016) - E. Klontzas, Michail; I. Kenanidis, Eustathios; J. MacFarlane, Robert; Michail, Theodoros; E. Potoupnis, Michael; Heliotis, Manolis; Mantalaris, Athanasios; Tsiridis, Eleftherios
ABSTRACT: Introduction : The need for fracture healing enhancement for the management of fracture complications such as non-union and for the achievement of early function in fracture patients is constantly increasing. Therefore, the development and evaluation of novel pharmaceutical agents is mandatory in order to accelerate the process and increase bone union rates. Areas covered : This review summarizes the most recent knowledge on the pharmacological enhancement of fracture repair. It provides a synopsis of the most important preclinical and clinical studies published over the past five years on long bone fracture healing. Expert opinion : To date, limited drugs seem to have the potential for clinical use in fracture healing enhancement and the field is progressing very slowly. Among anti-osteoporotic drugs, only PTH and anti-sclerostin antibodies have such a potential but further research is needed before clinical use. The same applies also to BMPs, the use of which still carries major drawbacks that should be overcome before their widespread clinical utilization. Other drugs and growth factors, such as statins, VEGF, FGF, EPO, could be future key players in fracture healing but evidence is still lacking. Further in depth understanding of the healing process is essential in order to identify novel effective pharmacological agents.